Rice dwarf and low tillering 10 (OsDLT10) regulates tiller number by monitoring auxin homeostasis. (August 2020) - Wen, Xiaoxia; Sun, Lianping; Chen, Yuyu; Xue, Pao; Yang, Qinqin; Wang, Beifang; Yu, Ning; Cao, Yongrun; Zhang, Yue; Gong, Ke; Wu, Weixun; Chen, Daibo; et al.
Highlights: OsDLT10 affects the formation and outgrowth of axillary buds. OsDLT10 is specifically expressed in stem nodes. Local auxin content are extremely reduced after mutation. IAA treatment of high concentration can inhibit the expression level of OsDLT10. Abstract: Tiller number is a crucial agronomic trait that directly affects the number of effective panicles and yield formation in rice. Here, we report a semi-dwarf and low tillering mutant Osdlt10 ( dwarf and low tillering 10 ) that exhibited reduced tiller number, semi-dwarfism, increased grain width, low seed-setting rate, curled leaf tip and a series of abnormalities of agronomic traits. Phenotypic observations showed that Osdlt10 mutants had defects in tiller bud formation and grew slowly at the tillering stage. Map-based cloning revealed that LOC_Os10g41310 was the responsible gene for OsDLT10, which was subsequently demonstrated using the CRISPR/Cas9 system and a complementary experiment. Expression pattern analysis indicated that OsDLT10 was primarily expressed in the stem node, the basic part of axillary bud and leaf sheath, pulvinus. The hormone treatment investigation indicated that extremely high of exogenous auxin concentrations can inhibit the expression of OsDLT10 . Endogenous auxin content decreased significantly at the base of stem node and axillary bud in Osdlt10 mutants. The results showed that OsDLT10 was related to auxin. qPCR analysis results further showed that the expression levels of auxin transport genes (PINs) and early response genes (IAAs) were significantly increased. The expression levels of WUS-like and FON1 were substantially decreased in the Osdlt10 mutants. These results revealed that OsDLT10 played a critical role in influencing tiller number, likely in association with hormone signals and the WUS-CLV pathway, to regulate axillary bud development in rice.